Comparative Analysis of Methods for Rate Calculation of Third Party Liability Insurance (on French Example) - Payaslyan, Stepan (Bulletin of Yerevan University G: Economics, 2012)
Insurance of motor vehicles is one of the most popular types of insurance in the world. It is a system of relations in provision insurance services between the provider and the holder of insurance, where the insurance holders’ interests defense is related with the possession, use and disposition of motor vehicles. In many countries motor vehicle owners are obliged to have a contract of insurance for the responsibility of damaging a third person. In this article it is presented the analysis of allowed amounts of risk factors affecting insurance payments in Armenia, as well as comparative analysis of the same risk factors of insurance payments existing in France.